2014
DOI: 10.1148/rg.343125211
|View full text |Cite
|
Sign up to set email alerts
|

Adult Bile Duct Strictures: Role of MR Imaging and MR Cholangiopancreatography in Characterization

Abstract: Bile duct strictures in adults are secondary to a wide spectrum of benign and malignant pathologic conditions. Benign causes of bile duct strictures include iatrogenic causes, acute or chronic pancreatitis, choledocholithiasis, primary sclerosing cholangitis, IgG4-related sclerosing cholangitis, liver transplantation, recurrent pyogenic cholangitis, Mirizzi syndrome, acquired immunodeficiency syndrome cholangiopathy, and sphincter of Oddi dysfunction. Malignant causes include cholangiocarcinoma, pancreatic ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(63 citation statements)
references
References 92 publications
1
54
0
5
Order By: Relevance
“…In current study also, none of the cases (0%) had primary sclerosing cholangitis were detected. Katabathina et al (17) reported that, the incidence of primary sclerosing cholangitis in their study was (3.8 %). In the present study, the US couldn't detect anatomical variants in any case (0 %), while MRCP had detected anatomical variants in eight cases (26.7 %) out of thirty.…”
Section: Discussionmentioning
confidence: 84%
“…In current study also, none of the cases (0%) had primary sclerosing cholangitis were detected. Katabathina et al (17) reported that, the incidence of primary sclerosing cholangitis in their study was (3.8 %). In the present study, the US couldn't detect anatomical variants in any case (0 %), while MRCP had detected anatomical variants in eight cases (26.7 %) out of thirty.…”
Section: Discussionmentioning
confidence: 84%
“…También permite la visualización del árbol biliar y sus variaciones anatómicas. Sin embargo, se trata de un procedimiento invasivo, con morbilidad reportada hasta en un 7% de los casos 11 , por lo que se reserva para casos en donde se necesite realizar algún procedimiento terapéutico.…”
Section: Discussionunclassified
“…Внедрение современного высокотехнологи-ческого медицинского оборудования в хирур-гическую практику позволило существенным образом улучшить качество диагностики и лечения заболеваний органов гепатогастробили-арной зоны [1,2]. Наряду с этим увеличивалось и количество интра-и послеоперационных ос-ложнений, среди которых наиболее трагичным для хирурга и пациента является повреждение желчных протоков (ПЖП) [2].…”
Section: Introductionunclassified
“…Наряду с этим увеличивалось и количество интра-и послеоперационных ос-ложнений, среди которых наиболее трагичным для хирурга и пациента является повреждение желчных протоков (ПЖП) [2]. При открытой холецистэктомии случайные ятрогенные ПЖП составляют 0,1-1% [3], при лапароскопических операциях -0,4-3,5% и даже 7% [4].…”
Section: Introductionunclassified